PEMBINGKAIAN BERITA RESHUFFLE MENTERI BULAN JUNI 2022 DALAM PORTAL BERITA ONLINE KOMPAS.COM DAN CNNINDONESIA.COM - Ananto, Bernadius Tyas; Herwandito, Seto (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
ABSTRACT This study aims to find out how the online media Kompas.com and CNNIndonesia,com frame the ministerial reshuffle news for June 2022. The method used in this study is a qualitative method. In this study, researchers used data collection methods by means of documentation. The unit of observation in this study is the framing of the June 2022 ministerial reshuffle news on the online news portals Kompas.com and CNNIndonesia.com. Meanwhile, the unit of7 analysisis the ministerial reshuffle news for June 2022 which is analysed using Robert. N Entman’s framing theory. The primary data comes from the ministerial reshuffle news for June 2022 on Kompas.com and CNNIndonesia.com. For secondary data comes from books, articles, and scientific journals.Thes results of the study show that Kompas.com considers that thus ministerial reshuffle is due to the vacancy of 10 deputy ministerial positions in Indonesia Maju cabinet. Meanwhile CNNIndonesia.com provided information that the ministerial reshuffle was Presiden Jokowi’s political nterst ahead of 2024. The results of the research also showed similarities that Kompas.com and CNNIndonesia,com emphasized the replacementof ministerial and deputy ministerial figures. Keywords: Framing, News, Online media, Reshuffle